January Effect and Size Effect Market Anomalies on Banking Companies in Indonesia Stock Exchange - Kenneth, Sean; Sumani, Sumani (International Business Management - Universitas Ciputra, 2024)
In the capital market, each stock price must reflect all available and relevant information or commonly known as the efficient market. In an efficient market, market anomalies should not occur to affect abnormal returns. This study aims to test whether the Indonesia Stock Exchange (IDX) exhibits January Effect and Size Effect anomalies, which could indicate inefficiencies in the capital market. The population includes all banking stocks listed on the IDX from 2018 to 2022, with a final sample of 38 banks after excluding incomplete data. The method involves examining both the January Effect with the Wilcoxon Signed Rank Test and the Size Effect with the Paired Samples T-test. The results indicate no significant January Effect during the 2018-2022 period, except in 2021, and no Size Effect anomalies for banking stocks during the same period.